Conversion of coal fly ash into glass-ceramics by controlled thermal treatment - Biljana Angjusheva,Emilija Fidancevski, Vojo Jovanov (My University, 2021)
Glass-ceramics were fabricated by controlled crystallization of glass vitrified without any additives from coal fly ash. The glass transition temperature (Tg) and peak temperature (Tp) of the parent glass were 580 ºC and 1020 ºC, respectively. The crystallization tendency of the parent glass was estimated by the Hruby-coefficient (KH = 2.3). The ratio of the crystalline and amorphous phases in the glass-ceramics sintered at 1100 ºC/60 min was 68/32. The major crystalline phases were calcium aluminum silicate (an orthite) and hematite. The density, bending strength, and E-modulus of the glass-ceramics were 2.20 g/cm3,78 MPa, and 32 GPa, respectively. The glass-ceramics can potentially be used as a construction material
Keywords: coal fly ash; vitrification; parent glass; consolidation; glass-ceramics